FAKTOR-AKTOR YANG MEMPENGARUHI AKUNTABILITAS PENGELOLAAN DANA DESA - Sari, Rada Ratna; Putri, Annie Mustika; Azmi, Zul (Balance : Jurnal Akuntansi dan Bisnis, 2022)
This study aims to provide evidence regarding Village Fund Management. In particular, this study examines the effect of apparatus competence, community participation, internal control and organizational commitment on village fund management accountability. This research is an empirical study using quantitative methods based on secondary data. The sample selection of this study used a purposive sampling method with a total of 127 questionnaires distributed in Kapur IX District. The test of this study used SPSS Version 20. It was used in data analysis and hypothesis testing. The results of this study found that the competence of the apparatus, community participation, internal control, and organizational commitment have an effect on the accountability of village fund management